Novel Ligands Targeting α4β1 Integrin: Therapeutic Applications and Perspectives - Baiula, Monica; Spampinato, Santi; Gentilucci, Luca; Tolomelli, Alessandra (Frontiers in Chemistry, 2019)
Among the other members of the adhesion molecules' family, α4β1 integrin, a heterodimeric receptor, plays a crucial role in inflammatory diseases, cancer development, metastasis and stem cell mobilization or retention. In many cases, its function in pathogenesis is not yet completely understood and investigations on ligand binding and related stabilization of active/inactive conformations still represent an important goal. For this reason, starting from the highlight of α4β1 functions in human pathologies, we report an overview of synthetic α4β1 integrin ligands under development as potential therapeutic agents. The small molecule library that we have selected represents a collection of lead compounds. These molecules are the object of future refinement in academic and industrial research, in order to achieve a fine tuning of α4β1 integrin regulation for the development of novel agents against pathologies still eluding an effective solution.